Strength and Deformation Characteristics of Reconstituted Sand under Different Stress Paths in True Triaxial Tests - Hasbullah Nawir; Bagus Eko Prasetyo; Andhika Sahadewa (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
To improve the geotechnical stress